Oligo(dT) is not a correct native PAGE marker for single-stranded DNA - Kejnovská, Iva; Kypr, Jaroslav; Vorlícková, Michaela (Biochemical and biophysical research communications, 2007)
Polyacrylamide gel electrophoresis is a widely used method to study short DNA fragments in solution. It is, however, a relative method requiring length markers to assess mobility, shape, flexibility, and molecularity of the DNA structures of interest. In recent literature we have encountered the use of oligo(dT) fragments as the native PAGE length markers. We show here that this practice is inadequate because oligo(dT) migration is strongly retarded in native polyacrylamide gels. This conclusion is qualitatively true irrespective of the conditions of electrophoresis, oligo(dT) length, and gel concentration. Depending on their length, oligo(dT) fragments migrate 2--4 times slower than that would correspond to their nucleotide number. This leads to erroneous conclusions, e.g., determination of the number of associated molecules in guanine quadruplexes or other DNA complexes.
Keywords: Oligodeoxyribonucleotides; Electrophoresis, Polyacrylamide Gel; DNA, Single-Stranded; elektroforéza v polyakrylamidovém gelu; jednovláknová DNA; oligodeoxyribonukleotidy